HIV Surveillance in a Large, Community-Based Study: Results from the Pilot Study of Project Accept (HIV Prevention Trials Network 043) - Piwowar-Manning E. (2017)
Background: Project Accept is a community randomized, controlled trial to evaluate the efficacy of community mobilization, mobile testing, same-day results, and post-test support for the prevention of HIV infection in Thailand, Tanzania, Zimbabwe, and South Africa. We evaluated the accuracy of in-country HIV rapid testing and determined HIV prevalence in the Project Accept pilot study.Methods: Two HIV rapid tests were performed in parallel in local laboratories. If the first two rapid tests were discordant (one reactive, one non-reactive), a third HIV rapid test or enzyme immunoassay was performed. Samples were designated HIV NEG if the first two tests were non-reactive, HIV DISC if the first two tests were discordant, and HIV POS if the first two tests were reactive. Samples were re-analyzed in the United States using a panel of laboratory tests.Results: HIV infection status was correctly determined based on-in country testing for 2,236 (99.5%) of 2,247 participants [7 (0.37%) of 1,907 HIV NEG samples were HIV-positive; 2 (0.63%) of 317 HIV POS samples were HIV-negative; 2 (8.3%) of 24 HIV DISC samples were incorrectly identified as HIV-positive based on the in-country tie-breaker test]. HIV prevalence was: Thailand: 0.6%, Tanzania: 5.0%, Zimbabwe 14.7%, Soweto South Africa: 19.4%, Vulindlela, South Africa: 24.4%, (overall prevalence: 14.4%).Conclusions: In-country testing based on two HIV rapid tests correctly identified the HIV infection status for 99.5% of study participants; most participants with discordant HIV rapid tests were not infected. HIV prevalence varied considerably across the study sites (range: 0.6% to 24.4%).Trial Registration: ClinicalTrials.gov registry number NCT00203749. © 2011 Piwowar-Manning et al; licensee BioMed Central Ltd.